Pengaruh Modal Intelektual pada Rasio Price to Book Value - Suryarahman, Erlangga; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 22 No 2 (2018)DO - 10.24843/EJA.2018.v22.i02.p10, 2018)
The purpose of this research is to examine the effect of intellectual capital consisting of value added capital employed (VACA), value added human capital (VAHU) and structural capital value added (STVA) on price to book value ratio. This study uses secondary data from all companies listed on the Indonesia Stock Exchange in 2016 with a population of 539 companies. The method of determining the sample is simple random sampling with the determination of the number of samples using Slovin formula that gives 230 companies. Hypothesis testing in this research is done by multiple linear regression analysis technique with a significance level of 5 percent (0.05). The analysis results show that VACA and STVA have a positive effect on price to book value ratio, while VAHU has no effect on price to book value ratio. Suggested for the company, should pay attention to the management of capital employed and structural capital so that resources are used effectively and can create value added for the company. Keywords: Profitability, growth opportunity, liquidity, capital structure, firm value